Quantification of Miconazole Nitrate and Eugenol in Formulated Emulgel by Planar Chromatography along its Stability Studies - Zanwar, Aarti Sachin; Sen, Dhanya B; Vyas, Pruthvi Hiteshkumar; Burle, Sushil Sureshrao; Ruikar, Dipti Bipinchandra; Sen, Ashim Kumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Fungal infections are rapidly increasing and combination therapy using Miconazole Nitrate (MCZ) and Eugenol (EGN), may offer a promising approach for developing new antifungal medications. Objectives: The purpose of the demonstrated work was to develop and validate a stability-indicating HPTLC method for concurrent measurement of MCZ and EGN in formulated emulgel. Materials and Methods: The separation technique of the HPTLC method was aided by pre-coated silica gel 60F254 on aluminium and toluene: ethyl acetate: methyl alcohol (18:1:1 v/v/v) as mobile phase. The quantification of MCZ and EGN in formulated emulgels along with their stability studies was conducted. Results: The optimised conditions were used to develop the spotted drugs and showed a linear response from 100-600 ng/band (r2=0.9995) for MCZ at Rf value of 0.33 and 53-318 ng/band (r2=0.9996) for EGN at Rf value of 0.70. Conclusion: The proposed validated work is suitable for the quantification of the above-cited drugs under various stress conditions and quality control purpose.
Keywords: Eugenol; Miconazole Nitrate; HPTLC; Emulgel; Topical formulation